Abundant organic nitrogen enhances natamycin biosynthesis by increasing NAD(P) metabolic pathway activity in Streptomyces gilvosporeus F607 - Meng, Zhihui; Yu, Minghui; Wang, Jiahui; Li, Haijun; Gao, Wenhui; Yang, Peitong; Cui, Xingyu; Zhang, Peipei; Fu, Jiafang; Cao, Guangxiang; Zong, Gongli (Frontiers in Microbiology, 2025)
Natamycin, a polyene macrolide antifungal produced by several Streptomyces species, is widely used as an industrial mold inhibitor in food preservation. Although nitrogen source effects on its production have been extensively studied, its underlying regulatory mechanisms remain unclear. Using transcriptome and metabolome analyses, we found that natamycin production increase by 2.8-fold during cultivation of Streptomyces gilvosporeus F607 in organic nitrogen-rich medium, accompanied by upregulation of 10 genes involved in NAD(P) biosynthesis and corresponding elevations in the levels of NAD or NADP with 1.81-fold and 1.04-fold increases. A novel multisubstrate enzyme, designated nicotinic acid mononucleotide (NaMN) adenylyltransferase (NadDsg), was demonstrated to slightly favor nicotinamide mononucleotide (NMN) over NaMN. Supplementation of S. gilvosporeus F607 with 10 mg/L NMN and overexpression of a site-directed mutant enzyme (NadDsgRYKK, at positions of R17Y20K26R168) promoted natamycin biosynthesis by 43.1%, increasing production from 4.67 g/L to 6.68 g/L. These findings indicate that an abundance of organic nitrogen primarily enhances natamycin biosynthesis by elevating NAD(P) levels, providing valuable insights for medium optimization and strain engineering toward high-yield natamycin production.